Innate immune-inflammatory signaling milieu in myeloid leukemia and aging-associated clonal hematopoiesis pathologies - Bhowmik, Satyaki; Bose, Anwesha; Sengupta, Amitava (Frontiers in Immunology, 2025)
Age-related accumulation of somatic mutations in hematopoietic stem and progenitor cells (HSPCs), causing clonal hematopoiesis (CH), often precedes the development of hematologic malignancies. Chronic inflammation and aberrant cytokine expression that are common in aging, contribute to clonal expansion and genomic instability. Acute myeloid leukemia (AML) is an (epi)genetically and physiologically diverse malignancy, characterized by clonal proliferation and incomplete differentiation of HSPCs. The innate immune system, with pattern recognition receptors (PRRs), plays a pivotal role in maintaining hematopoietic homeostasis. Dysregulated signaling through PRRs disrupts hematopoiesis, fostering malignant cell proliferation. In addition, cytokines and interferons exert multifaceted effects on HSPCs, impacting their proliferation, differentiation, and survival. Therapeutic approaches targeting innate immune pathways, offer promising avenues for treating hematologic malignancies. Understanding the intricate crosstalk between innate immunity and hematopoiesis would provide insights into novel therapeutic strategies for combating hematologic malignancies, offering hope for improved patient outcomes and survival. In this review, we discuss about the malfunctioning innate immune-inflammatory axes in the context of abnormal hematopoiesis and the therapeutic approaches that are utilizing/targeting these pathways with efficacy. This review delves into the derangements of innate immune and inflammatory pathways implicated in the development of AML and myelodysplastic syndromes (MDS), shedding light on the therapeutic strategies targeting these pathways.